Whole exome sequencing identifies novel mutations of epigenetic regulators in chemorefractory pediatric acute myeloid leukemia. (February 2018) - Zhan, Di; Zhang, Yingchi; Xiao, Peifang; Zheng, Xinchang; Ruan, Min; Zhang, Jingliao; Chen, Aili; Zou, Yao; Chen, Yumei; Huang, Gang; Hu, Shaoyan; Wang, Qian-fei; et al.
Highlights: We have, for the first time, performed whole exome sequencing on a Chinese cohort of chemorefractory pediatric AML patients. Novel mutations of epigenetic regulators such as KDM5C, SRIT6, CHD4, and PRPF6 were identified in pediatric AML patients. Mutations involving epigenetic regulators, were collectively enriched as a group in primary chemo-resistance AML patients. Gain of new mutations in genes such as MVP, TCF3, SS18, and BCL10, may contribute to chemo-resistance at relapse. Abstract: Genomic alterations underlying chemotherapy resistance remains poorly characterized in pediatric acute myeloid leukemia (AML). In this study, we used whole exome sequencing to identify gene mutations associated with chemo-resistance in 44 pediatric AML patients. We identified previously unreported mutations involving epigenetic regulators such as KDM5C, SRIT6, CHD4, and PRPF6 in pediatric AML patients. Despite low prevalence in general pediatric AML, mutations involving epigenetic regulators including splicing factors, were collectively enriched as a group in primary chemo-resistance AML patients. In addition, clonal evolution analysis of secondary chemo-resistance AML patients reveals dominant clone at diagnosis could survive several course of intensified chemotherapy. And gain of new mutations in genes such as MVP, TCF3, SS18, and BCL10, may contribute to chemo-resistance at relapse. These results provide novel insights into the genetic basis of treatment failure in pediatric AML.